Stiffness nonlinearity in structural dynamics: Our friend or enemy? - Brennan, Michael John [UNESP] (Springer Nature, 2017)
The effects of nonlinearity, particularly stiffness nonlinearity, has been of concern to structural engineers for many years. Primarily this has been because this type of nonlinearity can cause unpredictable dynamics, and considerable effort is necessary to analyze nonlinear structures. Due to the constant drive to improve the performance and efficiency of structures and mechanical devices, engineers have recently started to investigate whether nonlinearity can be incorporated into structures to provide some benefit. This chapter discusses some of the problems that stiffness nonlinearity can cause, and gives three examples where this type of nonlinearity can be put to good use. The examples are in vibration isolators, vibration absorbers and energy harvesters. If the nonlinearity is introduced in an appropriate way then it should not have an adverse impact on probabilistic prognostics and health management of energy systems.
Keywords: Energy harvesting; Nonlinear vibrations; Vibration isolation